A child in the Holy Land - Mohadjer, Gisu (Bahá'í Publishing, 2022)
"A Child in the Holy Land is a collection of accounts from individuals who had the bounty, as children, of meeting the members of the Holy Family of the Bahá'í Faith-Bahá'u'lláh, 'Abdu'l-Bahá, Shoghi Effendi, the Greatest Holy Leaf, Munírih Khánum, and Rúhíyyih Khánum. Bahá'u'lláh was the founder of the Faith, 'Abdu'l-Bahá was His son, and Shoghi Effendi was the grandson of 'Abdu'l-Bahá. The Greatest Holy Leaf was Bahá'u'lláh's daughter, Munírih Khánum was the wife of 'Abdu'l-Bahá, and Rúhíyyih Khánum was the wife of Shoghi Effendi and later became a Hand of the Cause, or outstanding teacher of the Faith. These stories bring to life the sacred lives of these individuals so that the reader can get a small taste of what life was like in the holy household of the Prophet-Founder of the Bahá'í Faith"--